Equilibrium State of PAHs in Bottom Sediment–Water–Suspended Sediment System of a Large River Considering Freely Dissolved Concentrations. Issue 3 (1st May 2015) - Lai, Yunjia; Xia, Xinghui; Dong, Jianwei; Lin, Wenting; Mou, Xinli; Zhao, Pujun; Jiang, Xiaoman; Li, Zhihuang; Tong, Yali; Zhao, Yunling
Abstract : In natural waters, the equilibrium state of hydrophobic organic compounds among bottom sediment (BS), suspended sediment (SPS), and water is fundamental to infer their transfer flux and aqueous bioavailability. However, this type of information remains scarce and fragmented. This study systematically evaluated the equilibrium state of polycyclic aromatic hydrocarbons (PAHs) in the Yangtze River. Total and freely dissolved concentrations of the 16 priority PAHs in pore water and overlying water (including surface and near‐bottom) of the Yangtze middle reaches were investigated, as were the concentrations of attached PAHs in SPS and BS. Results showed that concentrations of total/freely dissolved PAHs, dissolved organic carbon (DOC), and SPS in surface water were not statistically different from those in near‐bottom water, and the DOC–water distribution coefficients of PAHs in pore water were not statistically different from overlying water. However, significant disequilibrium was found at the sediment–water interface; concentrations of total/freely dissolved PAHs in pore water were 1 to 2 orders of magnitude higher than those in overlying water. This study offers a complete analysis of the potential disequilibrium of PAHs in BS–water–SPS system of large rivers and suggests that distribution of hydrophobic organic compounds between BS and overlying water is essential in controlling their equilibrium state in the BS–water–SPS system of natural waters.